Bis‐4, 4′‐biphenyl Ring Embedded Octaphyrin with Three Distinct Conformational Structures. Issue 56 (18th September 2019) - Chitranshi, Sangya; Adinarayana, B.; Das, Mainak; Cha, Won‐Young; Kim, Dongho; Srinivasan, A.
Abstract: Three distinct conformational structures of carbaoctaphyrins were prepared by incorporating bis‐4, 4'‐biphenyl units in the macrocyclic core. The free‐base form adopts a figure‐eight conformation, whereas the protonation triggers a conformational change with a pyrrole ring inversion and acquires an open‐framework structure. The insertion of bis‐Rh I metal ion in the macrocyclic core affords a singly twisted conformational structure. Furthermore, the local aromaticity in the bis‐4, 4'‐biphenyl ring dominates the overall macrocyclic aromaticity in all three forms, and thus adopts nonaromatic characteristics. These results are supported by spectral as well as theoretical studies, and they are unambiguously confirmed by X‐ray crystal analyses. Abstract : Structural assortment : Bis‐4, 4′‐biphenyl‐based octaphyrin was successfully synthesized. The figure‐eight conformation in the free‐base form changed to an open conformation by protonation, and to a singly twisted conformation by metalation. The spectral, structural and theoretical analyses revealed nonaromatic characteristics in all these forms.